Obtención de un extracto vegetal de la Ortiga mayor (urtica dioica) aplicando el método de maceración en frío para la elaboración de Queso fresco. - Quishpe Toapanta, Sandra Marisol (2019)
The present investigation was carried out ot Latacunga canton, Eloy Alfaro neighborhood, Salache Bajo neighborhood, in the Technical University of Cotopaxi, on academic laboratories of Agroindustrial Engineering career, whose main objective was to obtain a plant extract from the greater nettle (Urtica dioica) using the leaves and stems in fresh and dried applying the method of cold maceration and then use it as vegetable rennet in the fresh cheese production. The raw material was collected, selected and cleaned, old and diseased leaves were removed, the selected parts were washed and drained, then dried in an oven at 40ºC for 24 hours, then crushed in a mortar to reduce its size, it was macerated in distilled water and at different times (12 and 24 hours), both dry and fresh parts were left to rest in a cool, dark place, then the liquid was filtered and then centrifuged at a speed of 4000 rpm for 10 minutes and finally the obtained liquid was packed in a flask amber and it was kept at 4ºC. A complete random design was performed with two repetitions. For the functional analysis the Tukey test was used at 5%, this allowed through a statistical analysis in the Infostat 2018 software, to determine the best treatment resulting in the treatment t1 (a1b1c1) corresponding to Leaves + 12 hours + fresh, evaluated in the variables: pH, acidity, protein and rennet strength. The obtained results for pH was that t1 (a1b1bc1) reached a pH value of 5.25; in acidity it obtained an average of 1.78% and for rennet strength it reached an average of 5.77N; It is concluded that the use of fresh leaves at a time of maceration of 12 hours allows obtaining of the vegetable rennet of greater nettle for the elaboration of fresh cheese.